ZACHMAN'S FRAMEWORK IN THE INVENTORY INFORMATION SYSTEM ARCHITECTURE BASED ON WEB SERVICE - resa khoerunnisa (Universitas Nusa Putra, 2019)
Inventory is an activity that aims to manage the inventory of office or company assets owned. Inventory information systems have been widely used or developed in a place with a variety of technologies and systems. The problems that exist in YASTI (Tarbiyah Islamiyah Foundation) are the absence of a special, comprehensive and integrated Information System regarding the management of inventory data which often results in data redundancy (multiple data) between institutions and foundations. Also, requests for submission of goods that seem slow conveyed that can affect student service in providing facilities. According to the author, one of the best solutions to the above problems is the need for an inventory information system and in designing the system, an enterprise architecture inventory information system model is needed to minimize failure when implementing the system while running as needed. the modeling used UML diagrams, the analytical method in this study uses the Zachman framework which provides a foundation in helping provide the basic structure of the organization so that it can help design and develop an organization's information system. The design of the system generated in the Zachman framework will be a web-based inventory information system that can be used for information service issues. Keywords : Inventory, Zachman Framework, UML, Web